1993
DOI: 10.1111/j.1365-2249.1993.tb07981.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of adenosine deaminase in mitogen-stimulated lymphocytes

Abstract: SUMMARYAdenosine deaminase (ADA) expression on the surface of mitogen-stimulated lymphocytes was studied by flow cytometry. The gate for lymphocytes was located by cell size (forward scatter), cytoplasmic complexity (side scatter) and by expression of the markers CD2, CD4, CD8 and CD 19. After mitogenic proliferation two populations appeared, one corresponding to non-stimulated cells, and the other consisting of larger cells which showed relatively high expression of adenosine deaminase on their surface. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Our preliminary studies demonstrated that PPDB‐stimulated PBMC from M. bovis infected cattle exhibited increased cell size (>600 FSC) and granularity concomitant with an up‐regulation of IL‐2R, indicating that these changes are associated with immune cell activation. Similar findings have been reported in in vitro stimulated peripheral blood lymphocytes of rats (28) and humans (29). Consequently, in this study, cells were analyzed for their size (>600 FSC) as well as their surface marker expression in order to determine which cell population was activated after PPDB stimulation.…”
Section: Resultssupporting
confidence: 89%
“…Our preliminary studies demonstrated that PPDB‐stimulated PBMC from M. bovis infected cattle exhibited increased cell size (>600 FSC) and granularity concomitant with an up‐regulation of IL‐2R, indicating that these changes are associated with immune cell activation. Similar findings have been reported in in vitro stimulated peripheral blood lymphocytes of rats (28) and humans (29). Consequently, in this study, cells were analyzed for their size (>600 FSC) as well as their surface marker expression in order to determine which cell population was activated after PPDB stimulation.…”
Section: Resultssupporting
confidence: 89%
“…Thus, ecto-ADA was detected in Ͼ80% of T cells in some donors (nϭ14), whereas low or null percentages were detected in others (nϭ10). Ecto-ADA expression in lymphocytes analyzed with a pure or FITC-conjugated polyclonal anti-calf ADA Ab, which has been extensively described [6,12,20,27], presented an Ab-( Fig. 3B) and donor-dependent variability (nϭ37; range, 31-79 of ADA ϩ cells).…”
Section: Resultsmentioning
confidence: 71%
“…We have reported before that on treatment with mitogens or anti-CD3 antibodies, cell surface ADA expression increases [27]. Here, PHA-and anti-CD3-activated lymphocytes were used to study the effect of IL-12 on cell surface ADA expression.…”
Section: Resultsmentioning
confidence: 99%
“…2,73 In turn, lymphocyte activation causes MCAD activity to increase. 74,75 This can explain the increase in MCADA activity during HD. The low MCADA activity we found before HD may be the result of a tolerance phenomenon.…”
Section: Discussionmentioning
confidence: 94%